TRANSFER PRICING DAN CARA MENCEGAH TRANSFER PRICING AGAR TIDAK MELAKUKAN PENGGELAPAN PAJAK - EDY FIRMANSYAH; METYRIA IMELDA HUTABARAT; NIRWANA DEWI HARAHAP (JURNAL ILMIAH MAKSITEK, 2020)
This free trade, also cannot benefit both countries in terms of state income for taxation, where transactions carried out, eitherbetween governments or through multinational companies, sometimes they do not comply with the provisions of taxationbetween countries, so the transactions carried out are carried out to avoid paying taxes that are high. by conducting transferpricing transactions that are not in accordance with the laws and regulations. In 2019 the tax revenue set by the Governmentof Indonesia was 1,677.11 Trillion, but the realization of tax revenue was 1.312 Trillion, where the realization grew by 84%.This is influenced by not only obedience to paying taxes, but also efforts made systematically by creating transactions so thatthe amount of tax collected does not match, where this is done by several automotive companies in Indonesia that determinethe price of fixed asset sales transactions (transfer pricing). ) which is not in accordance with the stated fair value. Theresearch method used is descriptive qualitative with those sourced from literature studies. The results of the study state thatwhat companies must do so that transfer pricing transactions do not harm a country's tax revenues is to carry out taxplanning so that the transactions carried out are adjusted to the laws and regulations of a country, so as not to harm taxrevenues. that country, as well as conducting an advanced pricing agreement to the tax authority holder in a country, wherethis agreement is carried out so that transfer pricing transactions are carried out in accordance with the provisions stipulatedby the taxation law in a country, so that the country is able to increase its tax income. In addition, the tax authorities in acountry can prevent transactions that can minimize tax income by preventing transfer pricing that is detrimental to taxrevenues, by tightening transactions that are not permitted in transfer pricing for tax avoidance by setting criteria, terms andtypes or methods. transactions that can be made. In addition, the Director General of Taxes also changed the tax law byimplementing a derivative article from the law in the Minister of Finance regulation which was made to adjust the transferpricing transaction method that can be tolerated in order to increase tax revenue.